Tipografia e interação digital: linguagem gráfica aplicada em projetos no contexto dinâmico e participativo - PALOS, Karine Itao (2018)
This research is focused on the typographic object used as visual resource in the graphic language, which, when manipulated by the user, assumes nonlinear, permutative and interactive characteristics. Digital environments enable atypical typographic character behaviors, such as dynamicity and feedback. In this context, the aim of this research is to observe how interactivity with typographic objects can enhance user experience and the understanding of the contents represented in the project, in visual works. The methodology is based on the bibliographical reviews and concept discussions raised by three main authors: Vilém Flusser (2008), Julio Plaza (2003) and Alex Primo (2007). In the 1980s, the design philosopher Flusser (2008) discussed issues related to the loss of space in writing, increased image production and loss of links with the physical world of phenomena. In the 1990s, the media artist Plaza (2003) defined and contextualized the concept of interaction and interactivity, relating them to physical and digital media. Subsequently, a study on communication interaction, carried out by the communication scientist Primo (2007), explored the issue of digital interaction, by categorizing it into two categories, ‘reactive interaction’ and ‘mutual interaction’. We demonstrate how all discussions raised by the cited authors relate to typography production in the digital environment, since the typographic object is characterized as an information vehicle and may follow interactive trends. The set of ideas formed the basis for the analyses of projects that invite users to interact with typography. The chosen projects were: Cent mille milliards de poèmes (1961), Ensaio Sem Título (2016), Poemóbiles (1974), Gogoame (2016), Jogo Looksley’s Line Up (2010), Between Page and Screen (2016), Lettree (2004), Pyrographie (2005), Hilos (2006), Falling in Love (2016), He liked Thick Word Soup (2014), This is not a poem (2011), RE: Mark (2002) and TextRain (1999).